2D‐ERT Survey for the Identification of Archaeological and Historical Structures beneath the Plaza of Santo Domingo, Mexico City, Mexico. Issue 3 (19th December 2016) - Paz‐Arellano, Pedro; Tejero‐Andrade, Andrés; Argote‐Espino, Denisse
Abstract: Santo Domingo public square (Plaza of Santo Domingo) is located in Mexico City's downtown area. The history of its transformations began in pre‐Hispanic times and is still being written. The objectives of this investigation were to establish the position of the northwest corner of the ancient Mexica wall and to determine whether the Plaza became a public square during pre‐Hispanic or colonial times, taking into account the contradictions of the historical sources. For this purpose, we implemented three 80‐m‐long electrical resistivity tomography (ERT) profiles in the Plaza and one on the eastern side of the Church of Santo Domingo de Guzmán. A Wenner–Schulmberger array was designed for the data acquisition. The results could support the hypothesis that the Plaza of Santo Domingo was designed and constructed as an open public area in colonial times, since the observations in the electric profiles beneath the square could reveal the presence of a pre‐Hispanic structure. This structure could be part of the wall that surrounded the Mexica ceremonial compound. At the eastern side of the Dominican church, the foundations of the first Spanish chapel were identified, as well as portions of modern concrete deposits injected into the subsoil to stabilize the constant subsidence of the building. Copyright © 2016 John Wiley & Sons, Ltd.